Idiosyncratic risk and the cost of capital: The case of electricity networks - Dominik Schober; Stephan Schäffler; Christoph Weber (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
We analyze the treatment and impact of idiosyncratic or firm-specific risk in regulation. Regulatory authorities regularly ignore firm-specific characteristics, such as size or asset ages, implying different risk exposure in incentive regulation. In contrast, it is common to apply only a single benchmark, the weighted average cost of capital (WACC), uniformly to all firms. This will lead to implicit discrimination. We combine models of firm-specific risk, liquidity management and regulatory rate setting to investigate impacts on capital costs. We focus on the example of the impact of component failures for electricity network operators. In a simulation model for Germany, we find that capital costs increase by approximately 0.2 to 3.0 percentage points depending on the size of the firm (in the range of 3% to 40% of total cost of capital). Regulation of monopolistic bottlenecks should take these risks into account to avoid implicit discrimination.
Keywords: G32; G33; L51; L94; 330; Idiosyncratic/firm-specific risk; discrimination; incentive-based and quality regulation; liquidity management; size effects; electricity networks